Comparison of Physics-Based Optimization Algorithms by Using Benchmark Functions - Kiziloluk, Soner; Ozer, Ahmet Bedri (Ieee, 2016)
Many of meta-heuristics optimization algorithms which are used to solving optimization problems are inspired from biological evolution, physical, social and chemical processes. Electromagnetism-like Algorithm (EM), Big Bang-Big Crunch Algorithm (BB-BC) and Gravitational Search Algorithm (GSA) are investigated in this study and they are physics-based meta-heuristics techniques. Performances of EM, BB-BC and GSA are compared by using Rastrigin, Rosenbrock and De Jong test functions.
24th Signal Processing and Communication Application Conference (SIU) -- MAY 16-19, 2016 -- Zonguldak, TURKEY
Keywords: electromagnetism-like algorithm; big bang-big crunch algorithm; gravitational search algorithm